The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1536/ihj.17-289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palliative Care for Patients with Heart Failure

Abstract: Palliative care might be beneficial to heart failure. However, the results remain controversial. We conducted a systematic review and meta-analysis to explore the effect of palliative care on heart failure.PubMed, Embase, Web of Science, EBSCO, and Cochrane library databases were systematically searched. Randomized controlled trials (RCTs) assessing the effect of palliative care versus usual care on heart failure were included. Two investigators independently searched articles, extracted data, and assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Major depression is a common comorbidity in patients with heart failure [30][31][32] and results in poor quality of life, an increased risk for hospitalization, and mortality. [33][34][35][36][37][38][39] A vast majority of heart failure patients have symptoms of depression and anxiety. 3) Depressive symptoms show a strong negative impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Major depression is a common comorbidity in patients with heart failure [30][31][32] and results in poor quality of life, an increased risk for hospitalization, and mortality. [33][34][35][36][37][38][39] A vast majority of heart failure patients have symptoms of depression and anxiety. 3) Depressive symptoms show a strong negative impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced HF, also defined as stage D HF, is refractory to medical treatment, especially when patients have coexisting chronic renal failure. [1][2][3][4][5] Under these conditions, extra-and/or intracorporeal renal replacement therapy can improve cardiorenal hemodynamics. It reduces the intravascular volume, corrects acid-base and electrolyte imbalances, and removes uremic toxins, including cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…eart failure (HF) is a progressive disorder whose treatment options are limited and typically ineffective once patients develop end-stage HF. [1][2][3][4] Mortality is especially high when such patients have coexisting chronic renal failure. 5) Under these conditions, extra-and/or intracorporeal renal replacement therapy can improve the cardiorenal hemodynamics.…”
mentioning
confidence: 99%
“…Besides the conventional parameters that we selected in this study, various prognostic factors have been reported. [41][42][43] In the next study, we will reselect parameters for the analysis, considering also the multicollinearity.…”
Section: Deterioration Of Dlco In Patients With Stable Chronic Hf-alvmentioning
confidence: 99%